Green chemistry and anti-inflammatory activity of silver nanoparticles using an aqueous curcumin extract - Atheer A. Khashan; Yousaf Dawood; Yousif H. Khalaf (Results in Chemistry, 2023)
Rat models are sensitive to the induction of arthritis with adjuvants. Therefore, they are beneficial for studying this pathogenesis through the induction of adjuvant arthritis by injection of Complete Freund's Adjuvant (CFA). An eco-friendly green chemistry approach was utilized to synthesize silver nanoparticles (AgNPs) using an aqueous extract of curcumin root as a capping and reducing agent. AgNPs formation was evaluated by X-ray diffraction (XRD), scanning electron microscopy (SEM), and UV–vis spectroscopy analyses. The study aims to assess in vivo inhibitory effect of AgNPs on complete Freund’s adjuvant-induced arthritis in rats. Therefore, male albino rats were divided into four groups: Normal control; arthritic rats untreated; arthritis rats received standard drug (dexamethasone) as a positive control for 14 days; and arthritis rats received 100 mg/kg AgNPs for 14 days. The results showed that the AgNPs exhibit anti‑inflammatory effects in rats arthritis model by reducing the edema and levels of interleukin‑6 (IL-6) and high-sensitive C‑reactive protein (hs-CRP) in the paw tissues compared to the arthritic rats untreated. Overall, these findings evidence that the AgNPs have a potential promising anti‑inflammatory effect against arthritis disease.